THE ADSORPTION OF Pb(II) AND Cr(III) BV POLVPROPVLCALlX[4]ARENE POLVMER Adsorpsi Pb(lI)dan Cr(lII)oleh Polimer Polipropilkaliks[4]arena - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
ABSTRACT A research has been conducted to investigate the adsorption behavior of Pb(lI) and Cr(lll) onto polypropylcalix[4]arene polymer. The polypropylcalix[4]arene polymer was synthesized in the presence of H2S04 catalyst and chloroform under N2 condition for 5 h using 25-allyloxy-26,27,28-trihydroxycalyx[4]areneas the precursor. The Polymer was obtained as yellow crystal with melting point of 288-290 °C and its relative molecular weight was 44.810 g.mor1. The application of polypropylcalix[4]arene for. trapping heavy metal cations and its adsorption model were examined by stirring the suspension of the calixarene in the sample solutions for various pH, time, and concentration of Pb(lI) and Cr(lll) solution. Effect 'of pH on batch experiments for the mentioned ions indicated that the optimumpH for metal binding were 5 for lead(lI) and chromium(III). The adsorption model of metal ions on polypropylcalix[4]arene followed both the pseudo second order adsorption of Ho's and Lanpmuir isotherm adsorption kinetics models with rate constant (k) were 6.81 x 101min-1for Pb(lI) and 2.64 x 10-2min- for Cr(lll). The adsorption equilibrium constant, K, were 5.84 x 1r1 L.mor1for Pb(lI) and 4.66 x 1r1L.mor1for Cr(lll). The maximum adsorption capacity of polypropylcalix[4]arene to Pb(lI) and Cr(lll) were 16.31 and 18.14 mg.g-1with adsorption energy of 32.90 and 32.34 kJ.mor1,respectively. Keywords: polypropylcalix[4]arene,adsorption, Pb(II), and Cr(lll)